2006
DOI: 10.1634/theoncologist.11-1-39
|View full text |Cite
|
Sign up to set email alerts
|

Lung Cancer Highlights from ASCO 2005

Abstract: Learning ObjectivesAfter completing this course, the reader will be able to:1. Discuss the results of recent trials on the addition of a molecularly targeted agent to standard first-line chemotherapy in NSCLC.2. Explain the role of surgery in the treatment of stage III NSCLC.3. Discuss the current status of adjuvant chemotherapy in NSCLC. Access and take the CME test online and receive 1 AMA PRA category 1 credit at CME.TheOncologist.com CME CME This material is protected by U.S.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
2

Year Published

2006
2006
2012
2012

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 40 publications
0
3
0
2
Order By: Relevance
“…However, in most cases, the disease has progressed to an advanced stage upon diagnosis [1] . For advanced NSCLC, platinum-based combination chemotherapy is the mainstay of the treatment [2][3][4] .…”
Section: Introductionmentioning
confidence: 99%
“…However, in most cases, the disease has progressed to an advanced stage upon diagnosis [1] . For advanced NSCLC, platinum-based combination chemotherapy is the mainstay of the treatment [2][3][4] .…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, Ohta et al reported a 5-year survival rate of 27.1% in single level N2-disease NSCLC patients and suggested that initial operation had yet to be validated for patients with this disease [19]. Nevertheless, 5-year survival rates of non-surgery arms reported by some randomised studies range from 14% to 20% and did not exceed 30% [4,5]. In fact, many surgeons dissect mediastinal lymph nodes in an en bloc fashion and intra-operative designation of each nodal station might be confusing and difficult.…”
Section: Discussionmentioning
confidence: 99%
“…Thereafter, it has been believed that NSCLC patients with ipsilateral mediastinal nodal metastasis could not benefit from surgical resection alone, and thus multimodal treatments, such as neo-adjuvant chemotherapy followed by surgery or chemoradiotherapy, have been introduced. Recent randomised studies have shown that multimodal treatment including surgery arm was not superior to that including radiation therapy [4,5]. Current lung cancer treatment guidelines published by the National Comprehensive Cancer Network (NCCN) and American College of Chest Physicians (ACCP) excluded surgical resection from the initial treatment option in biopsy-proven stage IIIA NSCLC [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…L'addition de bé vacizumab a gé né ralement é té bien tolé ré e, cependant il faut noter un taux lé gè rement plus é levé de leucopé -nie. Les é pisodes d'hé moptysies sont rapporté s chez six patients dont quatre en sont dé cé dé s. Tous les cas sont rattaché s à un saignement de la tumeur notamment pour des tumeurs centrales [2]. L'é tude de phase II randomisé e, publié e en 2003, a permis de mettre en é vidence pour les cancers du rein mé tastatiques l'inté rê t du traitement par anti-VEGF.…”
Section: Inhibition De L'angiogenè Se Dans Les Cancers Pulmonaires Nounclassified
“…Dickler à l'ASCO 2004 a rapporté les ré sultats de l'association erlotinib (150 mg/j per os continu) et bé vacizumab (15 mg/kg tous les 21 jours) en phase II pour les patientes atteintes d'un cancer du sein mé tastatique. Six des 18 patientes ont pré senté une stabilisation de leur maladie et une ré ponse partielle [2].…”
Section: Inhibition De L'angiogenè Se Dans Les Cancers Du Sein Mé Tasunclassified